The Influence of E-Service Quality and Price Perception on Purchase Decisions in Tokopedia E-Commerce Among Students of Politeknik Negeri Kupang - Mangngi, Rabe; Mooy, Dikky (CV. Jala Berkat Abadi, 2025)
consumer behavior from conventional shopping to e-commerce, where electronic service quality (e-service quality) and price perception have become important factors influencing purchasing decisions. Tokopedia, as one of the largest e-commerce platforms in Indonesia, faces challenges in maintaining customer satisfaction amid intense competition. This study aims to determine the influence of e-service quality and price perception on purchasing decisions on Tokopedia, with a case study on students from the Business Administration Department, Company Management Study Program, at the State Polytechnic of Kupang. The sample consisted of 65 respondents. The research method used is quantitative with a survey approach, and the data analysis technique was carried out using multiple linear regression with SPSS.